Kebijakan Pemerintah Indonesia Terkait dengan Diplomasi di Kawasan Timur Tengah (Studi Hubungan United Arab Emirates - Israel) - Nur Rizki Eka Putra; Rakha Ridhyu Rasyadan; Nur Achmada Shaka Ramadhan; Intan Safitri (Universitas Indo Global Mandiri, 2024)
This research discusses the Indonesian Government's Policy Related to Diplomacy in the Middle East Region. The aim of the research is to understand the origins of the UAE-Israel relationship, the normalization process, and its implications for Southeast Asian countries, particularly in the context of Indonesian policy. The method used is library research with qualitative descriptive analysis, relying on secondary data from various literature sources. The results of the research show that the normalization of this relationship has created a positive climate for cooperation between the UAE and Southeast Asian countries, especially Indonesia, which also plays an important role. However, this normalization process has also triggered opposition from several countries that consider it contrary to their commitment to Palestine. The recommendation of this research is that both Indonesia and the UAE can act as more active mediators in resolving the Israel-Palestine conflict and enhance economic and diplomatic cooperation with Southeast Asian countries to create regional stability.